Art of Seduction: How Customer Experience Drives Attitudinal Loyalty and Online Impulse Buying on Shopee - Tanzil, Felicia; Rofianto, Whony; Simatupang, Batara Maju; Surjaatmadja, Surachman (Jurnal Ekonomi, Manajemen dan Perbankan (Journal of Economics, Management and Banking), 2025)
This study examines the influence of multiple dimensions of the online customer experience on attitudinal loyalty and online impulsive buying behavior, with self-control and time scarcity serving as moderating variables. Employing a quantitative methodology, data were collected via surveys from 85 Shopee users in the Jabodetabek area. The results indicate that trust, platform design quality, ease of navigation, and interactivity significantly enhance customer loyalty to Shopee. These results highlight the importance of a reliable and user-friendly online environment in fostering strong customer commitment and repeat engagement. The findings provide practical insights for e-commerce stakeholders by showing how optimizing trust, usability, and engagement can increase transaction frequency and customer retention. Ultimately, this research underscores the critical role of experiential factors in shaping online consumer actions and offers strategic recommendations for Indonesian e-commerce platforms to sustain competitive advantage through enhanced customer experiences.Overall, the study underscores the critical role of experiential factors in shaping consumer behavior online and offers actionable recommendations for leveraging these dimensions to improve both customer loyalty and sales performance within the Indonesian e-commerce sector.